The History and Development of Doctor of Health Science (DHSc) Programs in the United States - Past, Present, and Future: Part II: Present - Comparing DHSC Programs. - Ewing, Helen; Davis, Richard; Danielsen, Randy D.; Sauers, Eric; Reesal, Robin (Internet Journal of Allied Health Sciences & Practice, 2024)
Purpose: This three-part article series will advance the understanding of the Doctor of Health Science (DHSc) programs in the United States. Method: Part I discussed relevant historical information about Higher Education and the Doctor of Philosophy (PhD) to reach this goal. It described the transition of PhD philosophies to professional doctorates by following the historical postgraduate program paths in Education, Nursing, and Public Health. There was a brief discussion about the rapid growth of professional doctorates. Part I ended by identifying the origins of DHSc programs in the United States. Part II looks at the evolutionary stages of professional doctorates and DHSc programs. This section compares the DHSc degree to a PhD degree and examines the recent state of DHSc programs. Part III discusses present and future trends among DHSc programs in the United States. It focuses on workplace expectations of doctorate graduates, changing learner demographics and needs, essential curriculum designs for students, competency-based learning and assessment for future learners, the design of culminating projects critical for prospective DHSc learners, and the importance of third-generation style DHSc programs. Conclusion: These are the first papers that record the origins, development, current state, and trends of DHSc programs in the United States.